2013
DOI: 10.1111/pere.12021
|View full text |Cite
|
Sign up to set email alerts
|

Partner preferences across sexual orientations and biological sex

Abstract: This study examined how partner preferences differ across interpersonal contexts (romantic attachment and relationship expectations) based on sexuality and biological sex. Participants completed measures of attachment and behavioral expectations for their romantic partners, cross‐sex friends, and same‐sex friends. The attachment anxiety results revealed an effect of sexuality: Single heterosexuals scored higher for their cross‐sex friends than same‐sex friends, single lesbian/gay individuals scored higher for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 53 publications
(119 reference statements)
1
9
0
Order By: Relevance
“…For example, Ueno et al (2009) found no differences in emotional closeness depending on LGB youth's friends' sexual orientation, and the benefit of higher‐quality friendships for better mental health also did not differ. However, LGBTQ+ people may have different expectations for the quality of their friendships depending on sex and gender: lesbians have lower expectations for emotional closeness in their friendships with heterosexual men than gay men have for heterosexual women (Willis, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Ueno et al (2009) found no differences in emotional closeness depending on LGB youth's friends' sexual orientation, and the benefit of higher‐quality friendships for better mental health also did not differ. However, LGBTQ+ people may have different expectations for the quality of their friendships depending on sex and gender: lesbians have lower expectations for emotional closeness in their friendships with heterosexual men than gay men have for heterosexual women (Willis, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Parents are more likely to educate their daughters than to educate their sons on how to deal with other people's emotional states. As such, people are significantly more likely to seek out straight and gay women for emotional support and least likely to seek out straight men (Willis, 2014).…”
Section: Punctuation and Sexmentioning
confidence: 99%
“…Attachment researchers have increasingly investigated which attachment relationships are more predictive of desirable psycho-social outcomes than others, and the degree to which relationship-specific attachment models differ (Klohnen et al, 2005;Overall et al, 2003;Shaver et al, 1996;Willis, 2014). Given that attachment research suggests that romantic partners become primary attachments in adulthood, this study considered how the romantic attachment may be a protective factor for LG individuals in a way that unsupportive parents are not, and in a way that is uniquely different from heterosexuals.…”
Section: Attachment Patterns For Lesbian/gay Individuals With Unaccep...mentioning
confidence: 99%
“…These styles include a sense of security, and dimensions of avoidance and anxiety (Brennan et al, 1998;Fraley & Shaver, 2000). More recently, however, attachment theorists have noted that this 'relatively stable anchor' can be adjusted as a consequence of significant events or circumstances (Bowlby, 1988;Hazan & Shaver, 1987;Cozzarelli et al, 2000;Overall et al, 2003;Sibley & Overall, 2008;Willis, 2011;Willis, 2014). Attachment patterns tend to change as a function of romantic status, indicating that lovers become an additional primary attachment figure (Eastwick & Finkel, 2008;Fraley & Shaver, 2000;Trinke & Bartholomew, 1997;Willis, 2011;Willis, 2014).…”
Section: Attachment Theorymentioning
confidence: 99%
See 1 more Smart Citation